PROSES PEMBELAJARAN METODE BERMAIN PERAN (ROLE PLAYING) DALAM MENINGKATKAN KECERDASAN INTERPERSONAL PADA ANAK USIA DINI DI PAUD LENTERA - Shaliha, Shafa Nabila; Muis, Abdul; Santika, Tika (IKIP Siliwangi, 2025)
This study aims to discuss the learning process of role playing method in improving interpersonal intelligence in early childhood at Paud Lentera. The research method uses qualitative type and case study approach. The subjects of this research are the Principal of Paud Lentera, Class B1 and B2 Teachers, and class B parents. Data collection techniques through observation, interviews, and documentation. The sampling technique was purposive sampling. Data analysis using Miles Huberman analysis. The results of the research obtained are developing students' thinking and reasoning power. In this method the teacher can find the talents, uniqueness, character, intelligence of the students. So students are encouraged to be able to socialise rules, learn what is learned in family life. In addition, in interpersonal intelligence there are 3 components, namely; first, social insight is that students have self-awareness about being aware of thoughts, feelings, and surrounding situations, introduction to social norms, student skills in solving problems. Second, namely social sensitivity, students have an empathetic attitude in their school and home environment, instilling prosocial attitudes in early childhood. Third is social communication, there are students' skills in communicating clearly and effectively and students' skills in listening clearly and effectively.